Is there scope for better individualisation of anthracycline cancer chemotherapy?. Issue 2 (30th November 2020) - Sallustio, Benedetta C.; Boddy, Alan V.
Abstract : Anthracyclines are used to treat solid and haematological cancers, particularly breast cancers, lymphomas and childhood cancers. Myelosuppression and cardiotoxicity are the primary toxicities that limit treatment duration and/or intensity. Cardiotoxicity, particularly heart failure, is a leading cause of morbidity and mortality in cancer survivors. Cumulative anthracycline dose is a significant predictor of cardiotoxicity risk, suggesting a role for anthracycline pharmacokinetic variability. Population pharmacokinetic modelling in children has shown that doxorubicin clearance in the very young is significantly lower than in older children, potentially contributing to their higher risk of cardiotoxicity. A model of doxorubicin clearance based on body surface area and age offers a patient‐centred dose‐adjustment strategy that may replace the current disparate initial‐dose selection tools, providing a rational way to compensate for pharmacokinetic variability in children aged <7 years. Population pharmacokinetic models in adults have not adequately addressed older ages, obesity, hepatic and renal dysfunction, and potential drug–drug interactions to enable clinical application. Although candidate gene and genome‐wide association studies have investigated relationships between genetic variability and anthracycline pharmacokinetics or clinical outcomes, there have been few clinically significant reproducible associations. Precision‐dosing of anthracyclines is currently hindered by lack of clinically useful pharmacokinetic targets and models that predict cumulative anthracycline exposures. Combined with known risk factors for cardiotoxicity, the use of advanced echocardiography and biomarkers, future validated pharmacokinetic targets and predictive models could facilitate anthracycline precision dosing that truly maximises efficacy and provides individualised early intervention with cardioprotective therapies in patients at risk of cardiotoxicity.